Trauma system regionalization improves mortality in patients requiring trauma laparotomy. Issue 1 (January 2017) - Schechtman, David; He, Jack C.; Zosa, Brenda M.; Allen, Debra; Claridge, Jeffrey A.
Abstract : INTRODUCTION: This study evaluates the impact of a regional trauma network (RTN) on patient survival, intensive care unit (ICU) length of stay, and hospital length of stay in patients who required trauma laparotomy. METHODS: Patients who required trauma laparotomy from January 2008 to December 2013 were analyzed. Patients admitted during 2008–2009 and 2011–2013 were designated as pre-RTN and RTN groups, respectively. The primary outcome was mortality. RESULTS: A total of 569 patients were analyzed, 231 patients were pre-RTN, and 338 were in the RTN group. Overall, mean age was 35.7 ± 17.1 and median Injury Severity Score was 16 (25th–75th percentile: 9–26). The two groups were similar with regard to age, Injury Severity Score, Abbreviated Injury Scale abdomen, sex, and mechanism. Overall, there was a 35% relative reduction in mortality from the pre-RTN to RTN group ( p = 0.035), and 30% more patients were triaged to a Level 1 trauma center in the RTN group ( p < 0.001). Logistic regression showed that being in the RTN group was an independent predictor for survival ( p = 0.026) with odds ratio of 0.53 (95% confidence interval, 0.30–0.93). Patients with penetrating trauma had a nonsignificant decrease in mortality and a reduction of 1 day of ICU stay ( p = 0.001). Patients with blunt trauma had a significant reduction in mortality from 38% in the pre-RTN group to 23% in the RTN group ( p = 0.017). CONCLUSION: This study focused on the unique patient population that required trauma laparotomies. It showed that trauma system regionalization led to a significant increase in the number of patients triaged to a Level 1 trauma center and reduction of ICU length of stay. More importantly, it demonstrated the benefit of regionalization by showing a significant reduction of hospital mortality in this critically injured patient population. LEVEL OF EVIDENCE: Therapeutic study, level IV.